The Advantage of Using Edmodo in English Instruction - Harahap, Khofifah; Rizqoh, Miftahu; Effendi, Susmitra Muhammad; Andriani, Weli; Ihsan, Muhammad Taufik (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
In this 21st century, technology-based learning has been the main concern in today’s learning process since the rising use of technology. Recently, students and teachers are expected to have decent knowledge of digital learning as one way to facilitate their learning process. One form of digital learning is using Edmodo in the classroom. So, it's important for teachers to make plans for English learning through Edmodo. The aim of this article is to provide information that consists of using Edmodo in planning English learning. The method used in writing this paper was literature-based and based on collecting data and information that related to Edmodo as a medium for learning English. The results indicate that there are many advantages to using Edmodo in planning English learning. As for the teacher, Edmodo promotes teachers to meet the needs of different students, supports a sense of community among students, makes them feel respected and important, and provides three useful standards, namely usability, accessibility, and compatibility.